Electrophysiological Properties of Human Cortical Organoids: Current State of the Art and Future Directions - Zourray, Clara; Kurian, Manju A.; Barral, Serena; Lignani, Gabriele (Frontiers in Molecular Neuroscience, 2022)
Human cortical development is an intricate process resulting in the generation of many interacting cell types and long-range connections to and from other brain regions. Human stem cell-derived cortical organoids are now becoming widely used to model human cortical development both in physiological and pathological conditions, as they offer the advantage of recapitulating human-specific aspects of corticogenesis that were previously inaccessible. Understanding the electrophysiological properties and functional maturation of neurons derived from human cortical organoids is key to ensure their physiological and pathological relevance. Here we review existing data on the electrophysiological properties of neurons in human cortical organoids, as well as recent advances in the complexity of cortical organoid modelling that have led to improvements in functional maturation at single neuron and neuronal network levels. Eventually, a more comprehensive and standardized electrophysiological characterization of these models will allow to better understand human neurophysiology, model diseases and test novel treatments.